Mineralogy and geochemistry of rare metal (Zr-Nb-Hf-Ta-REE-Ga) coals of the seam XXX of the Izykh Coalfield, Minusinsk Basin, Russia: Implications for more widespread rare metal mineralization in North Asia; International Journal of Coal Geology; Vol. 289 - Vergunov A. V. Aleksey Viktorovich; Arbuzov S. I. Sergei Iwanowitsch; Spears D. A. David Alan; Kholodov A. S. Aleksey Sergeevich; Iljenok (Il'enok) S. S. Sergey Sergeevich (2024, 2024)
Title screen